Kepemimpinan: Teori, Peran, Pendekatan dan Kualitasnya dalam Pendidikan - Fithroh, Indah Nur Af’idatun; Maelani, Evi; Tamsikudin, Tamsikudin (Jurnal Ilmiah Wahana Pendidikan, 2025)
Leadership is often seen as a hierarchical-command relationship between superiors and subordinates, often placing subordinates as powerless objects. Therefore, in this research, researchers want to try to examine the theories, functions, approaches and qualities of leadership that occur and are applied in the realm of education itself and become a benchmark for improvement and development towards a better direction in the realm of education, especially in terms of leadership. The method applied is a qualitative research method with a descriptive pattern which combines literature review and interviews as a data collection tool. From this research, data was produced that leadership theory in education includes trait, behavioral and environmental theories. In it there is a leadership role given by the leader of the school institution which focuses more on the example and participation of the staff and teachers themselves so that there is a series of business activities. Thus, choosing a transformation pattern combined with situationalism becomes the approach concept that is applied in this educational institution. Therefore, as an output from the approach applied, whether a leadership concept is quality or not is seen from the process that the institution goes through and the results obtained, whether the output is of higher quality, whether the use of learning models and media has been varied and integrated with technology and how professionalism of teachers serving at the school.